Pengaruh Promosi Berbasis Sosial Media dan Potongan Harga terhadap Keputusan Pembelian pada Alfamart W418 Desa Bandar Setia - Andi Rahman; Muhammad Hilman Fikri; Arief Hadian; Yayuk Yuliana (Universitas Batanghari Jambi, 2022)
The purpose of this study was to determine the effect of social media-based promotions and price discounts on purchasing decisions at Alfamart W418 Desa Bandar Setia. The population in this study were consumers of Alfamart W418 from January-March 2021 as many as 25,198 people. The sample in this study obtained by using the Slovin formula, based on the calculation of the minimum number of samples, if the behavior of a population is not known with certainty, then the number of samples can be determined as many as 100 people. This type of research is quantitative research. The data collection instrument used a questionnaire/questionnaire which was then analyzed using the multiple linear regression analysis method. From the results of this study there is an influence between social media-based promotions and price discounts on purchasing decisions at Alfamart W418 Desa Bandar Setia. With the results of the R square test of 0.649 which means 64.9% states that the variables based on social media promotions and price discounts have an effect on purchasing decisions of 64.9% while the remaining 35.1% is influenced by other variables not examined in this study.